Desirable Traits of a Good Biocontrol Agent against Verticillium Wilt - Deketelaere, Silke; Tyvaert, Lien; França, Soraya C.; Höfte, Monica (Frontiers in microbiology, 2017)
The soil-borne fungus causes serious vascular disease in a wide variety of annual crops and woody perennials. Verticillium wilt is notoriously difficult to control by conventional methods, so there is great potential for biocontrol to manage this disease. In this study we aimed to review the research about biocontrol to get a better understanding of characteristics that are desirable in a biocontrol agent (BCA) against Verticillium wilt. We only considered studies in which the BCAs were tested on plants. Most biocontrol studies were focused on plants of the , and and within these families eggplant, cotton, and oilseed rape were the most studied crops. The list of bacterial BCAs with potential against was dominated by endophytic and isolates, while non-pathogenic xylem-colonizing and isolates topped the fungal list. Predominant modes of action involved in biocontrol were inhibition of primary inoculum germination, plant growth promotion, competition and induced resistance. Many BCAs showed antibiosis and mycoparasitism but these traits were not correlated with activity and there is no evidence that they play a role . Good BCAs were obtained from soils suppressive to Verticillium wilt, disease suppressive composts, and healthy plants in infested fields. Desirable characteristics in a BCA against are the ability to (1) affect the survival or germination of microsclerotia, (2) colonize the xylem and/or cortex and compete with the pathogen for nutrients and/or space, (3) induce resistance responses in the plant and/or (4) promote plant growth. Potential BCAs should be screened in conditions that resemble the field situation to increase the chance of successful use in practice. Furthermore, issues such as large scale production, formulation, preservation conditions, shelf life, and application methods should be considered early in the process of selecting BCAs against .